Sirolimus in combination with low-dose extended-release tacrolimus in kidney transplant recipients - Zou, Zhi-yu; Dai, Lin-rui; Hou, Yi-bo; Yu, Chen-zhen; Chen, Ren-jie; Chen, Yan-yan; Liu, Bin; Shi, Hui-bo; Gong, Nian-qiao; Chen, Zhi-shui; Chen, Song; Chang, Sheng; et al. (Frontiers in Medicine, 2023)
Many challenges remain for long-term survival of renal allografts. Once-daily sirolimus (SRL) combined with low-dose extended-release tacrolimus (LER-TAC) may improve medication adherence and reduce the potential nephrotoxicity of calcineurin inhibitors (CNI) compared with standard immunosuppression regimens, thus potentially improving long-term graft survival. This retrospective, observational, single-center, propensity score matching (PSM) study compared conversion to SRL combined with low-dose ER-TAC and mycophenolic acid (MPA) combined with standard-dose TAC in kidney transplant recipients. After PSM, there were 56 patients in each group. Efficacy, safety, and medication adherence were evaluated over 12 months. There was no significant difference between the two groups in terms of graft and recipient survival and incidence of biopsy-proven acute rejection (P=1.000), and none of the recipients developed dnDSA after conversion. The mean eGFR improved in SRL+LER-TAC group after conversion compared to before conversion (51.12±20.1 ml/min/1.73m2 vs 56.97±19.23 ml/min/1.73m2, p<0.05). The medication adherence at 12 months after conversion was superior to before conversion (p=0.002). Our findings suggest that an immunosuppressive regimen of SRL combined with low-dose ER-TAC is no less effective and safe than standard immunosuppressive regimens for renal transplant recipients and may improve graft renal function and medication adherence.